Relação entre solos e vegetação em gradiente topográfico de fragmento de Floresta Atlântica - Machado, Luciana Ventura (2016)
Rainforests have known great diversity of plant species distributed in different vegetation types. This physiognomy diversity can result from high variation biogeochemistry, climate variability, topography, soil parent material, microbial activity, soil c